Determinação da vida de prateleira de filés congelados de piramutaba (Brachyplatystoma vailiantii, VALENCIENNES,1840). - Filgueiras, Lígia Amaral (Instituto Nacional de Pesquisas da Amazônia - INPA, 2002)
Piramutaba(Brachyplatystoma vaiílantii) is a very important fish to exportatlon In the Amazon region. The main states which exploit it are Amapá, Amazonas (highestamountcaughtin 1993-4.142tons)and Pará(main exportarstate).The present study was developed to establish the shelf life of frozen fillets of piramutaba during 120 days. Sensorial analyses as well as physic-chemical(pH, nitrogen of total volatile bases- N -TVB, water retaining capacity- WRC)and (Jmicrobiological analyses were determined periodically. The resuits indicate that ((j frozen fillets of piramutaba were keptfirst quality during the whole study.The fillets present lean fillets (fat = 1,31%)and presented 27% yield in relation to the weight without guts and head, which influences positively to a long shelf life, and of piramutaba used in this study in this period of the year was considered to Of consequentiy its importance as an exportatlon fish.
Keywords: Piramutaba; Brachyplatystoma vaillantii; Congelamento de pescado